Effects of Sustained Stretching with and without Kinesio Tapping in Relieving Spasticity in Spastic Cerebral Palsy - Iqra Tariq Khan, Sidra Khaliq, Sakina Shaikh, Aliya Shair Muhammad, Syeda Rida-E-Zainab, Shama Zulfiqar, Maryam Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
The study was conducted to determine the effect of sustained stretch with and without kinesio tapping in spastic cp, Total of 28 patients were taken from Physiofitt blue area, Islamabad and Al-Nafees Medical College Hospital Islamabad. The data was collected through convenient sampling and patients were allocated randomly via lottery method. This study was initiated after approval from advanced study & research committee (ASRC) of Isra Institute of Rehabilitation Sciences, Isra University, Islamabad. The results in MAS score between KT group and non KT group in 0, 2nd and 4th week assessment were non-significant with the p-value of 0.57, 0.80 and 0.33 respectively and among non KT group and KT group 0, 2nd and 4th week assessment in ROM dorsiflexion the results were also non-significant with p- value 0.40, 0.07 and 0.059 respectively. Repeated measure ANOVA showed that in MAS score of non KT group the results were significant with the p-value between 2nd and 4th week assessment is 0.00, p- value between 0 and 4th week assessment is 0.03 and p-value between 0 and 2nd week assessment is 0.03 while in KT group the p-value between 2nd and 4thweek assessment is 0.00, p- value between 0 and 4th week assessment is 0.01 and p-value between 0 and 2nd week assessment is 0.01. Repeated measure ANOVA in ROM dorsiflexion in non KT group shows the significant results with the p-value between 2nd and 4th week assessment is 0.00, p- value between 0 and 4th week assessment is 0.00 and p-value between 0 and 2ndweek assessment is 0.00 while KT group also showed significant results with the p-value between 2nd and 4th week assessment is 0.00, p- value between 0 and 4th week assessment is 0.01 and p-value between 0 and 2nd week assessment is 0.01. Null hypothesis is accepted